Genetic parameters for wool traits in Finnsheep lambs - Puntila, Marja-Leena; Mäki, Katariina; Nylander, Anne; Rintala, Onerva (MTT Agrifood Research Finland, 2007)
Genetic parameters were estimated for wool characteristics of white and coloured Finnsheep. The data consisted of 5 309 lambs from ordinary production flocks, the Finnsheep nucleus flock and a breeding flock. The variance component estimation was done applying REML analyses. Wool traits included fleece uniformity, density, staple formation, lustre, crimp frequency, fineness grade and staple length. There was a smaller dataset that contained also lamb live weight, greasy fleece weight and additional fleece characteristics including fibre diameter measured with the OFDA method. The variance components for direct and maternal effects were estimated using bivariate analysis for 42-day, 120-day weight and greasy fleece weight. Heritability for visually assessed wool characteristics varied from 0.23 to 0.43 and for measured traits from 0.45 to 0.62. Staple length had a high negative genetic correlation with crimp frequency and fineness grade. Heritability of greasy fleece weight was high (0.55) and that of fibre diameter 0.62. The genetic correlation between crimp frequency and fibre diameter was negative (- 0.56). The results imply that the assessed traits are useful indicators for fleece quality and those of major importance can be introduced into the breeding programme. The results suggest that there is no antagonism in selection for both growth capacity and wool quantity.
Keywords: Ko; fibres; Finnsheep; genetic parameters; live weight; OFDA; wool characteristics